Application of Structural Model Analytic Synthetic to Early Reading and Writing Ability - Eva Oktavia; Sucipto Sucipto; Muhajir Muhajir; Soubar Isman (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2026)
This research is designed to investigate the impact of the Structural Analytic Synthetic (SAS) method on the early reading and writing abilities of first-grade elementary school students. This study uses a quasi-experimental design with a pretest-posttest control group framework, involving 50 first-grade students from Gili Anyar Elementary School, who were allocated into experimental and control groups using total sampling method. The experimental group was taught using the SAS model, while the control group used traditional techniques. Instruments, including initial reading and writing assessments, have undergone content validity evaluation by experts and reliability testing using the Cronbach Alpha coefficient. Data analysis was conducted using an independent sample t-test after confirming normality and homogeneity. The research findings indicate a significant difference between the two groups. The experimental group achieved an average posttest score of 77.52 in reading and 81.6 in writing, while the control group achieved scores of 42.00 and 45.12, respectively, with a p-value of less than 0.05. This data confirms that the SAS model, thru the structural, analytical, and synthesis stages, facilitates a more systematic understanding of the relationships between letters, syllables, words, and sentences for children. This research is novel because of the use of SAS in rural elementary schools, a subject that is rarely studied. The practical implication is that early-grade educators can use SAS as an alternative method to cohesively enhance early reading. Additional studies are recommended to increase the sample size, extend the duration of the intervention, and incorporate parental support and environmental elements to achieve more comprehensive results.